Development and drug release characterization of biodegradable polymeric ocular implants - Ho, Joey Sok Kuan. (2008)
Poly (L-lactic acid) of IV 1.63, 2.32 and 4.37 and poly(DL-lactic-co-glycolic acid) of IV 0.86 and 4.8 were cast into films using the solvent casting technique to fabricate an in situ sustained drug delivery ocular implant. The solvent cast films were degraded in phosphate buffered saline solution (PBS) and the medium was tested spectrophotometrically at regular intervals for the amount of drug, Ganciclovir (GCV) released. All of the drug-loaded films demonstrated a uni- phasic release pattern with the exception of PDLGA of IV 0.86 and PLGA of mixed IV (80 wt % PLGA of IV 4.8 and 20 wt % PDLGA of IV 0.86) films which displayed a bi-phasic release pattern.